Top Management Attributes, Psychological Capital, and Green Accounting Effectiveness in Public-Private Partnership Context - Chu, Chien-Chi; Ji, Yun; Lee, Hsiu-Yu; Lin, Yu-Ting (Frontiers in Psychology, 2019)
Through individual and/or collective psychological states affected by demographic attributes, top managers shape the corporate culture and determine the overall strategic directions of an organization. Thus, top management attributes affect the adoption of critical company-wide practices. This opinion paper discusses the implications of, and urges academic attention to, the role psychological capital plays in the relationship between top manager attributes and the effectiveness of green accounting practices adoption in a public-private partnership (PPP) context. Theoretical and practical implications are elaborated upon.